Investigating the Implementation of ChatGPT in English Language Education: Effects on Student Motivation and Performance Levels - Afkarin, Mohammad Yusfi; Asmara, Candra Hadi (Journey: Journal of English Language and Pedagogy, 2024)
In the era of rapid advancements in Artificial Intelligence (AI), ChatGPT (Chat Generative Pre-Trained Transformer) emerges as a pivotal tool reshaping educational landscapes. This research, based on self-determination theory, investigates how ChatGPT influences the motivation and academic performance of 35 seventh-semester English education students. Utilizing mixed methods, it contrasts the experiences of 25 ChatGPT users with those of 10 non-users. The quantitative analysis demonstrates notably higher levels of motivation and GPAs among ChatGPT users (with a mean motivation score of 44.88 and a mean GPA of 3.63) compared to non-users (with a mean motivation score of 17.60 and a mean GPA of 3.06). Qualitative insights highlight themes such as 'Improved Comprehension and Independent Learning' and 'Increased Academic Efficiency and Productivity,' illustrating how ChatGPT supports effective and thorough learning experiences. In keeping with the tenets of self-determination theory, these results demonstrate that ChatGPT has a beneficial effect on students' motivation. The study also recommends more experimental studies to investigate how students' motivation and performance can be improved by using ChatGPT.